2019
DOI: 10.1111/ecc.13044
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer survivors' challenges to returning to work: A qualitative study

Abstract: Objective To assess the challenges and needs of colorectal cancer (CRC) survivors in maintaining employment and returning to work (RTW) from the perspectives of both CRC survivors and employers in the United States. Methods Semi‐structured interviews with CRC survivors (n = 10) and employers (n = 4) were transcribed, coded and thematically analysed using NVivo 12 software. Results Workplace challenges for survivors included the following: inadequate availability of paid and unpaid leave, limited availability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Studies have also indicated the importance of support from the employers and colleagues. 30 Table 5 highlights the facilitators and barriers for employment status identified in studies that included CRC patients. 10,12,21,22,24,25,28,[31][32][33][34][35] The present study had a distinctly large sample size (N = 4408).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also indicated the importance of support from the employers and colleagues. 30 Table 5 highlights the facilitators and barriers for employment status identified in studies that included CRC patients. 10,12,21,22,24,25,28,[31][32][33][34][35] The present study had a distinctly large sample size (N = 4408).…”
Section: Discussionmentioning
confidence: 99%
“…However, some could not take leave or reduce hours due to their financial situation (e.g. Gruss et al, 2019).…”
Section: Return To Work (Rtw)mentioning
confidence: 99%
“…inability to provide flexible toilet breaks, limited leave availability) (e.g. Gruss et al, 2019 and some survivors were even fired or forced into retirement after treatment (e.g. Gruss et al, 2019).…”
Section: Return To Work (Rtw)mentioning
confidence: 99%
See 2 more Smart Citations